Activation of NF-ĸB in leukemic cells in response to initial prednisone therapy in children with acute lymphoblastic leukaemia: relation to other prognostic factors - Kamieńska, Elżbieta; Ociepa, Tomasz; Wysocki, Mariusz; Kurylak, Andrzej; Matysiak, Michał; Urasiński, Tomasz; Urasińska, Elżbieta; Domagała, Wenancjusz (Polish Journal of Pathology, 2011)
Nuclear factor ĸB (NF-ĸB) is a transcription regulator of proliferation and cell death. Increased activation of NF-ĸB may be responsible for treatment failure in children with acute lymphoblastic leukaemia (ALL). This study aimed to assess changes in NF-ĸB activation in peripheral blood mononuclear cells prior to and after 6 and 12 h of prednisone administration in relation to age, initial WBC count at diagnosis and early treatment response in childhood ALL. The study comprised 55 children with de novo ALL. Cells were stained with mouse anti-NF-ĸB (p65) antibody followed by goat anti-mouse antibody conjugated with FITC and measured by laser scanning cytometer. The nuclear/cytoplasmic (N/C) ratio of NF-ĸB reflecting activation of NF-ĸB was decreased 12 h after treatment in the standard risk group patients, whereas it remained statistically unchanged in the non-standard risk group patients. Changes in the N/C ratio of NF-ĸB were not associated with age and early treatment response; however, in children with an initial WBC count higher than 20 000/μl at diagnosis, this ratio was increased after 6 and 12 h from prednisone administration. The association of higher activation of NF-ĸB with an elevated initial WBC count suggests that activation of NF-ĸB may be responsible for treatment failure in children with ALL.